ANALISIS SENYAWA ANTIBIOTIK DARI JAMUR SIMBION YANG TERDAPAT DALAM ASCIDIANS Didemnum molle DI SEKITAR PERAIRAN BUNAKEN-SULAWESI UTARA - Bara, Robert A.; Kandou, Grace D.; Ola, Antonius R. B.; Posangi, Jimmy (JURNAL LPPM BIDANG SAINS DAN TEKNOLOGI, 2015)
Endosymbiont can be interpreted as microbes that live in colonies in the internal tissues of other higher organisms without causing adverse effects directly on the its host. Endosymbiont organisms have a huge potential to be exploited as a new natural products that are useful in medicine, agriculture, and industry. This research is focused on the antibacterial potential. Ascidians Didemnum moll speciments were collected from Manado waters. The fungal isolates were purified followed by screening their antibacterial activity towards Staphylococcus aureus and Pseudomonas aeruginosa. In this study we isolated 3 fungal specimens Acremonium sp. (ADMB-1, 2 and 3). Three isolates showed potential antibacterial activity. Together with the fungal isolates, we also isolated Bacillus galacosidilyticus from the same host. This bacterial isolate also show antibacterial potency.